The experiences of caregivers of children with epilepsy: A meta-synthesis of qualitative research studies - Yu, Zhichao; Shao, Qinwen; Hou, Kunhua; Wang, Yanjie; Sun, Xianghong (Frontiers in Psychiatry, 2022)
Abstract Aims: To explore the experiences of caregivers of children with epilepsy. Design: Qualitative studies were meta-synthesized. Data sources: Eight databases(PubMed, CINAHL, EMBASE, Web of Science, CNKI, Wanfang Data, VIP database, and CBM) were searched for qualitative studies from each database’s inception to 31 June 2021. Review methods: Studies were critically appraised using the Joanna Briggs Institute (JBI) Critical Appraisal Checklist for Qualitative Research. Qualitative data were extracted, summarized, and meta-synthesized. Results: Thirteen studies were included, and four themes were identified: (a) heavy burden of care; (b) emotional experience; (c) coping strategies; (d) care needs. Conclusion: Caregivers carried a heavy burden of care and psychological burden. Despite the adoption of different coping strategies, their emotional distress was still very serious. Caregivers had unmet care needs. In order to improve caregivers' care capacity, the society and healthcare workers need to provide them with information support, psychological support, and take measures to create a friendly medical and living environment for them.